Aktualisasi Pengetahuan Konten Pedagogi Guru Melalui Rencana Pelaksanaan Pembelajaran - Nissa, Ita Chairun (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2015)
What does it take to become a good teacher? This question if it was compared to the Act No. 14 Year 2005 on Teachers and Lecturers, then what is needed is four competencies that pedagogical competence, personal competence, social competence, and professional competence. The fourth of these competencies, actually can be built from simple things related to teachers' daily tasks. One of them is the task of designing a Lesson Plan. This task becomes mandatory duty for teachers before executing an instruction in the classroom. However, many teachers who do not wholeheartedly and is regarded as a liability solely educational administration. If we did so, many important lessons for teachers of design a Lesson Plan in developing Pedagogical Content Knowledge which is the basic building block of all four professional competence of teachers. Pedagogical Content Knowledge is knowledge of what and why the material was taught to students as well as how to teach it. Perhaps this seems trivial and often done daily by teachers, but whether we have actually done significantly ?. This article reveals how Pedagogical Content Knowledge can be built through the activity of designing a Lesson Plans.